Between promise and paradox: artificial intelligence in education, ethics, and the teacher’s role - Chinchilla-Valverde, Jorge Luis (2026)
This essay argues that AI in education is not merely a technical add-on but a shift in the pedagogical regime: from the ideal of automation to the horizon of mediation and co-agency. Its genealogy includes intelligent tutoring systems, learning analytics, and generative models, together with perceptions and realities of adoption, with particular attention to equity and the digital divide. The educational value of AI depends on ethical and governance conditions such as data protection and privacy, explainability and accountability, justice and inclusion, as well as clear limits on automated delegation. Drawing on recent frameworks, operational criteria are proposed for both classrooms and institutions: authorship and verification logs, meaningful human oversight, non-AI alternatives, and clear data rules. The teacher’s role is redefined as curator and mediator of processes with public evidence of reasoning, able to decide when to use, pause, or reject AI. The final reflection calls for aligning innovation with rights and strengthening initial and continuing teacher education in ethics and task design, so that personalization does not lead to new inequalities and schools preserve their function of judgment and deliberation.